Dance in Schools… What for? - do Valle, Flavia Pilla; Zancan , Rubiane Falkenberg (Revista Brasileira de Estudos da Presença, 2022)
The essay is a defense for the presence of dance in the curriculum of elementary and secondary education. Why should we have dance in schools? Dance in schools… What for? Based on the work developed over the years by the authors, which involved searching for articles, participating in lectures, writings, among other strategies, this text points to eight points of argument that can be unfolded and gathered in other configurations. As a conclusion, the importance of dance in elementary and secondary education is highlighted, as, in addition to legislation, it enables students to develop knowledge about their own bodies, instigating their creative capacity and expanding their historical and cultural horizons.